Thai nurses' perspectives on the use of complementary and alternative medicine among Thai breast cancer survivors in northern Thailand. Issue 2 (13th November 2013) - Wanchai, Ausanee; Armer, Jane M; Stewart, Bob R
<x xml:space="preserve">Abstract</x> Breast cancer survivors are more likely to seek complementary and alternative medicine (CAM) for their health and well‐being than other cancer patients. The purpose of the study was to describe how Thai nurses perceive the use of CAM in Thai breast cancer survivors. An ethno‐nursing research method was used. Fifteen Thai nurses who had experience in taking care of Thai breast cancer survivors who used CAM from a tertiary care referral and resource centre in the lower northern part of Thailand were interviewed. Two major themes emerged from this study: Meaning of care practices in CAM was seen as: (i) an additional beneficial choice for health; and (ii) emotional and psychological healing. Nurses should be concerned about CAM use in Thai breast cancer survivors. Open communication about CAM helps ensure that safe and holistic care is provided. Further research to enhance integration of CAM into health care is needed.